Correlation between IL-6 (Interleukin 6) and Laboratory Parameters (CRP, Total Proteins and LDH) for Verification of the Inflammatory Origin in Preeclampsia - Pejkovska Ilieva, Maja; Antovska, Vesna; Mirjana Kaeva Pejkovska (SHMSHM / AAMD, 2020)
In normal pregnancy there is a transfer to the Th2 anti-inflammatory type of immunity, directed toward the fetus and the placenta, whereas in pregnancy complications, such as preeclampsia due to absent transfer, Th1 or proinflammatory immune system is dominated. This article analyzes what are the most important circulating biomarkers created by syncytiotrophoblast that together combined and promote oxidative stress. An increase in proinflammatory and decline in the antiinflammatory cytokine is an imbalance that explains the theory that due to impairement of the immunological response, consequences on the mother's circulation are developed and are reflected in the manifestation of pregnancy complications such as preeclampsia and intrauterine growth restriction. The purpose of the study is to emphasize the importance of the results of the correlation between interleukin 6, measured in the serum of patients from 14 to 20 gestational weeks, with laboratory parameters that are pathognomonic for preeclampsia (LDH, total protein and CRP). This explains the immunological and inflammatory response in preeclampsia serving as a predictor of the condition. For that purpose, the materials and methods that were used were 100 patients examined at the University Clinic of Obstetrics and Gynecology, divided in two groups. The first or examined group consists of 50 patients with notch of the uterine artery present in the second trimester from 14 to 20 gestational weeks. The second, or control group consists of 50 patients with absent notch of the uterine artery. These patients are then referred to the Institute of Immunobiology and Human Genetics at the Faculty of Medicine in Skopje to examine the levels of cytokines, in particular the relationship between the proinflamatory with antiinflammatory cytokines (TNF-α, IL-6 vs. IL-10) using ELISA (enzyme-linked immunosorbent assay) methodology, with Magnetic Luminex Assay multiplex kit. The results between the examined and the controlled group verified an increase in proinflammatory (TNF-α and IL-6) and a decrease in the antiinflamatory cytokine (IL-10), from which the variance of the level IL-6 showed important statistical significance p<0.01. Positive correlation was of great statistical significance between levels of cytokine IL-6 and increased levels of LDH and CRP, and with decreased levels of the total proteins of the preeclamptic patients. (LDH p<0.00001, CRP p<0.025 and total proteins p<0.0012). The role of the inflammatory response is obtained by the correlation of the interleukins in the second trimester and laboratory examinations in the third trimester as a sufficient predictive method in detection in early stages the preeclampsia syndrome.
Keywords: preeclampsia; prediction; interleukins